If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5e + 7e + -9 + -1e = 84 + -4e Reorder the terms: -9 + 5e + 7e + -1e = 84 + -4e Combine like terms: 5e + 7e = 12e -9 + 12e + -1e = 84 + -4e Combine like terms: 12e + -1e = 11e -9 + 11e = 84 + -4e Solving -9 + 11e = 84 + -4e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '4e' to each side of the equation. -9 + 11e + 4e = 84 + -4e + 4e Combine like terms: 11e + 4e = 15e -9 + 15e = 84 + -4e + 4e Combine like terms: -4e + 4e = 0 -9 + 15e = 84 + 0 -9 + 15e = 84 Add '9' to each side of the equation. -9 + 9 + 15e = 84 + 9 Combine like terms: -9 + 9 = 0 0 + 15e = 84 + 9 15e = 84 + 9 Combine like terms: 84 + 9 = 93 15e = 93 Divide each side by '15'. e = 6.2 Simplifying e = 6.2
| (1/3)(1/3)(1/3)3=a | | 4/5y-8+=2/5+16 | | 8/2x=15/60 | | 7(k-3)= | | 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 | | 2.3=y+.9 | | 12c-48=84 |